Gaining a "normal life": HIV-positive Indonesian female injection drug users in drug recovery. Issue 1 (1st February 2021) - Yona, Sri; Ismail, Rita; Nurachmah, Elly; Levy, Judith; Norr, Kathleen
Abstract: The number of female injection drug users in Indonesia is rapidly increasing. This study explores the experiences of women living with HIV in recovery from heroin injection. Using a ground theory approach, 22 women former drug users in Jakarta participated in this study. Six themes emerged: the challenges of quitting, the role of self-motivation, the utility of methadone treatment, the importance of partner and family support, the transformation of "self" and situation, and the rewards of a normal life if successful. These women's accounts point to the personal and cultural challenges that they faced as women, wives, and mothers.